Paraguay: a housing finance proposal for middle- to low-income groups - J. Vicente Fruet Cardozo; Guzmán A. Muñoz Fernández (CEPAL Review, 2015)
The construction and ownership of homes is fundamental to economic development, the generation of wealth and the formation of the middle class. Although a number of studies have been conducted and programmes implemented in recent decades, there remains a significant housing deficit in Paraguay and Latin America, indicating that such programmes have been unsuccessful. For families unable to document a steady income, the main obstacle to homeownership is often financing. This paper aims to demonstrate the economic and financial feasibility—provided there is sufficient political will and coordination between public and private entities—of a project to build 75,000 homes for 300,000 people (4.5% of the Paraguayan population) with middle to low incomes. The median household income in this segment, for which there is a significant shortage of decent housing, is US 396.50. A maximum of US 63.44 per month may be set aside for housing costs.